2021
DOI: 10.1182/bloodadvances.2020003556
|View full text |Cite
|
Sign up to set email alerts
|

Autologous stem cell transplantation after anti-PD-1 therapy for multiply relapsed or refractory Hodgkin lymphoma

Abstract: Autologous stem cell transplantation (ASCT) can be curative for patients with relapsed/refractory Hodgkin lymphoma (HL). Based on studies suggesting that anti-PD-1 monoclonal antibodies (mAbs) can sensitize patients to subsequent chemotherapy, we hypothesized that anti-PD-1 therapy before ASCT would result in acceptable outcomes among high-risk patients who progressed on or responded insufficiently to ≥1 salvage regimen, including chemorefractory patients who are traditionally considered poor ASCT candidates. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 48 publications
4
29
1
1
Order By: Relevance
“…3,11 A ret ro spec tive anal y sis in 78 patients who progressed on one or more sal vage reg i mens and who were treated with reg i mens containing CPI showed favor able results, with 59% of patients achiev ing a CMR and a post-ASCT PFS of 81% at 18 months. 23 This sug gests that treatment with CPI may improve chemosensitivity of pre vi ously chemorefractory dis ease. Interestingly, pre-ASCT CMR sta tus was not sig nif cantly prog nos tic for post-ASCT PFS in this cohort, suggesting a PR might be suf f cient for pro ceed ing to ASCT after CPI in this patient pop u la tion.…”
Section: Patients With Pri Mary Refrac Tory Dis Easementioning
confidence: 90%
“…3,11 A ret ro spec tive anal y sis in 78 patients who progressed on one or more sal vage reg i mens and who were treated with reg i mens containing CPI showed favor able results, with 59% of patients achiev ing a CMR and a post-ASCT PFS of 81% at 18 months. 23 This sug gests that treatment with CPI may improve chemosensitivity of pre vi ously chemorefractory dis ease. Interestingly, pre-ASCT CMR sta tus was not sig nif cantly prog nos tic for post-ASCT PFS in this cohort, suggesting a PR might be suf f cient for pro ceed ing to ASCT after CPI in this patient pop u la tion.…”
Section: Patients With Pri Mary Refrac Tory Dis Easementioning
confidence: 90%
“…Additionally, in the chemotherapy regimen for R/R lymphoma, the DHAP regimen containing high-dose cytarabine is more efficient compared to non-Hodgkin's lymphoma (NHL) high-dose cytarabine, with both higher OS and PFS, thus increasing the efficacy of lymphoma (HL) treatment ( 7 ). Merryman et al ( 19 ) recently reported that PD-1 mAb bridged ASCT with conventional BEAM to treat R/R HL can make 18-month PFS reach 78%. Therefore, in the treatment of this patient, we reasonably combined the advantages of PD-1 and ASCT.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…In some cases, immune reprogramming ahead of transplant may lead to even better outcomes. Herrera and colleagues demonstrated that heavily pre-treated patients who received PD-1 therapy ahead of autologous stem cell transplant and responded had improved rates of progressionfree survival at 18 months compared to PD-1 non-responders (86% vs. 51%, [86]). Overall, more research is needed in order to clarify the potential benefits (i.e., increased graft vs. lymphoma effect) and risks (increased GVHD) associated with the use of CAR T cells and other immunomodulatory agents, such as PD-1 inhibitors, ahead of transplant [87].…”
Section: Interplay Of Transplant and Car T Therapymentioning
confidence: 99%